The presidency in the era of 24-hour news - Cohen, Jeffrey E. (Princeton, NJ : Princeton University Press, 2008)
The Presidency in the Era of 24-Hour News examines how changes in the news media since the golden age of television--when three major networks held a near monopoly on the news people saw in the United States--have altered the way presidents communicate with the public and garner popular support. - Publisher.
The growing disconnect between presidential news coverage and public opinion -- The presidential news system during the golden age of presidential television -- The new media age and the decline in presidential news -- Change in presidential news over the long haul : the New York times historical series, 1857-1998 -- The increasing negativity in presidential news in the age of new media -- Sources of negativity in presidential news during the age of new media -- The declining audience for news and the new media age -- Declining trust in the news media and the new media age -- The implications of the new media on the presidential news system and presidential leadership -- Conclusions : The new media, the Presidency, and American politics.
Includes bibliographical references (pages 233-249) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: USA -- Präsident; Presidents -- United States; Mass media -- Political aspects -- United States; Press and politics -- United States; Presidents -- Press coverage -- United States; United States -- Politics and government -- Press coverage; Présidents -- États-Unis.; États-Unis -- Politique et gouvernement -- Couverture de presse; POLITICAL SCIENCE -- Political Process -- Leadership; SOCIAL SCIENCE -- Media Studies; Mass media -- Political aspects; Politics and government -- Press coverage; Presidents; Presidents -- Press coverage; Press and politics; United States; Massenmedien; Berichterstattung